Global studies : - Ogden, Dr. Suzanne (McGraw-Hill, 2008)
Global Studies is a unique series designed to provide comprehensive background information and selected world press articles on the regions and countries of the world. Each Global Studies volume includes an annotated listing of World Wide Web sites and is now supported by an online Instructor's Resource Guide.